2021
DOI: 10.3390/economies9020046
|View full text |Cite
|
Sign up to set email alerts
|

Panic Buying and Consumption Displacement during COVID-19: Evidence from New Zealand

Abstract: Panic buying and hoarding behavior is a significant component of crisis- and disaster-related consumption displacement that has received considerable attention during the COVID-19 pandemic. Understanding such purchasing and stockpiling behavior provides critical information for government, disaster managers and the retail sector, as well as policy makers to adjust crisis response strategies and to better understand disaster management, including preparedness and response strategies. This study examines consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 58 publications
3
56
0
1
Order By: Relevance
“…Our main interest initial was the hyper consumption and in particular the panic consumption because the panic buying is driven by negative emotions and the COVID-19 pandemic is associated with such emotions. There are studies in this area, which are cases from specific context (Hall et al, 2021;Keane and Neal, 2021;O'Connell et al, 2020) and there is no world data available free on this topic. Thus, on this initial stage of the research, we focus on the overall consumption, measured by Domestic material consumption per capita (tons per capita) 4 .…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Our main interest initial was the hyper consumption and in particular the panic consumption because the panic buying is driven by negative emotions and the COVID-19 pandemic is associated with such emotions. There are studies in this area, which are cases from specific context (Hall et al, 2021;Keane and Neal, 2021;O'Connell et al, 2020) and there is no world data available free on this topic. Thus, on this initial stage of the research, we focus on the overall consumption, measured by Domestic material consumption per capita (tons per capita) 4 .…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Thus, an intriguing direction for scholars to focus on would be on possible cultural contingencies of unneeded consumption behaviour. For example, with peaks at Christmas, Easter and Black Friday, the quantities of consumption will increase which is not caused by disaster-related panic event [ 9 ]. Future research must control the influence of the Chinese Spring festival in COVID-19 on unneeded consumption behaviour and test the recovery level of such behaviour more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Unneeded consumption is different from panic buying. Panic buying is caused by the object of acquiring security and preparing for future needs [ 9 ]. Unneeded consumption is activated by the habitual trend or relieving stress after lockdown [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specific studies reporting consumer’s pet food preferences and buying behavior in 2020–2021 during the COVID-19 pandemic are rather limited [ 23 , 25 ]. However, numerous studies reported general changes in consumer behavior as a result of the disruptions of COVID-19 and restrictions on social life, including shopping [ 53 , 54 , 55 , 56 , 57 ]. These changes included several forms of unusual behavior leading to empty shelves and product shortages [ 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the coronavirus pandemic, there was a focus on gratitude towards essential workers and compassion towards consumers while they were forced to stay at home [ 59 ]. Other reasons for brand switching were product scarcity or changes due to income constraints as a result of redundancy and unemployment [ 53 ]. Pet owners may have actively switched brands during the COVID-19 pandemic for affordability reasons or because they felt that the brand promise was betrayed.…”
Section: Introductionmentioning
confidence: 99%